BCL11A Polymorphism in Egyptian Children with β-Thalassemia: Relation to Phenotypic Heterogeneity - Salah, Nouran Y.; Ali, Heba G. A.; Bassiouny, Noha; Salem, Lamya; Taha, Sara I.; Youssef, Mariam K.; Annaka, Layla; Barakat, Noha M. (Journal of Pediatric Genetics, 2021)
Fetal hemoglobin (HbF) is a potent genetic modifier of β-thalassemia phenotype. B-cell lymphoma 11A (BCL11A) gene results in significant silencing of HbF. The aim of this study was to assess the prevalence of different BCL11A genotypes among a cohort of Egyptian children with β-thalassemia and to correlate them to HbF and clinical severity score. Eighty-two children with β-thalassemia (aged 12.95 ± 3.63 years) were recruited from the Pediatric Hematology Clinic, Ain Shams University. They were divided based on the clinical severity of β-thalassemia into three subgroups: 20 mild (24.4%), 24 moderate (29.3%), and 38 severe (46.3%). Age, gender, age of diagnosis, initial HbF level, transfusion history, and history of splenectomy were assessed. Anthropometric measures, signs of anemia and hemosiderosis, and the severity score were determined. Laboratory investigations such as complete blood picture, ferritin, and single gene polymorphism genotyping of the rs11886868 were also performed. Our findings showed that 16 children had CC genotype (19.5%), 38 had TC genotype (46.3%), and 28 had TT genotype (34.1%) of the rs#. β-thalassemia children with TT genotype had significantly higher severity scoring than the other two groups (p < 0.001). Moreover, mean initial HbF was found to be lower in children with TT genotype followed by TC and CC genotypes (p < 0.001). Increased γ-globin expression associated with BCL11A gene polymorphism is associated with better clinical severity of β-thalassemia.
Keywords: BCL11A polymorphism; β-thalassemia; phenotypic heterogeneity